Detection by PCR of human papillomavirus in Colombia: Comparison of GP5+/6+ and MY09/11 primer sets (2011)
The aims of this study were to determine the prevalence of HPV infection and evaluate the concordance and performance of two primer sets for detecting single and multiple viral infections. A total of 1810 Colombian women were enrolled in the study, and molecular, cytological and epidemiological analyses were performed. Both concordance and performance of two different PCR amplification primer sets (GP5+/6+ and MY09/11) were assessed. The results showed that 60.2% of females with positive HPV DNA were infected by more than one viral type. The OR for multiple infections was 18.2 when using the MY09/11 primer set and 6.52 with the GP5+/6+ primer set. The results also showed an association between GP5+/6+ positivity and the severity of the disease regarding the cytological findings. It was also found that using a single primer set led to underestimating the prevalence for HPV infection. The simultaneous use of these primer sets is an important tool for the detection of HPV DNA, being equally relevant for identifying multiple infections and low viral DNA copies. This study highlights the importance of suitable assessment of HPV epidemiological profiles; screening programs must also be strengthened to broaden the coverage of the most vulnerable populations. © 2011 Elsevier B.V.